IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXTS THROUGH READING ALOUD STRATEGY AT SMP NEGERI 1 ERIS - Sang Ayu Putu Desy Herdiyanti Putri; Merlin M. Maukar; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2023)
The aim of the study was to find out whether or not students' reading comprehension of narrative texts might be enhanced by using the reading aloud strategy. The Reading Aloud Strategy is a reading exercise that uses a loud voice reading style to help kids concentrate and pay attention. 20 students from the VII grade at SMP Negeri 1 Eris made up the sample for this quantitative study. The researcher employed a pre-experimental design with one group pre-test and post-test design. Multiple-choice examinations, true-false quizzes, and essays served as the research tools in this study. Using the average score algorithm, the research's data were statistically analyzed. The data calculated using the students' pre-test results was 49, and the test was 78 after. Between the pre-test and post-test, there was a 29 point change in the pupils' scores. According to the study's findings, the pre-average test's score was lower than the post-average test's score. The researcher draws the conclusion that the reading aloud strategy works well to increase pupils' reading comprehension.